Contextual-Based Bulletin as Media for Learning Renewable Energy - Susetyo, Gayuh; Sarwanto, Sarwanto; Sukarmin, Sukarmin (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2024)
Physics is a science that teaches about physical phenomena. To make it easier for students to learn physics in the Merdeka curriculum, appropriate media for learning. "Profil Pelajar Pancasila" in the Merdeka curriculum is Indonesia's response to the 21st-century education paradigm to increase students' critical thinking. This research aimed to determine the effect of contextual learning media in bulletins and PowerPoint on contextual critical thinking ability in terms of curiosity. The research instruments were formative assessment, curiosity questionnaire, contextual teaching module, bulletin, and PowerPoint. The research used an experimental method, which was held in classes of 10 senior high schools; one control class used PowerPoint, and another class used a bulletin as an experiment class. Before the study was done, those instruments were tested in different schools. Data that were taken for this research were critical thinking using assessment and curiosity using questionnaires, but the researcher also documented the study through videos. The data was analyzed using IBM SPSS Statistics and Microsoft Excel, including questions on validity and reliability, normality, homogeneity, two-tailed t-tests, two-way analysis of variance, effect size, and Scheffe. Based on research, using contextual bulletin has a better effect on critical thinking than using learning media, which teachers, namely PowerPoint, always use. The student's results can be improved through innovative media, and this study proves that it effectively increases students' critical thinking by using bulletins as media. This study can become a reference for Merdeka curriculum learning, and the teacher can use it in the school to enrich and enhance the media references that will be used.